The Symptoms of Herbicidal Action: The Case of Aclonifen - Kılınç, Özgür Kıvılcım (Turkish Journal of Agriculture - Food Science and Technology, 2015)
The symptoms which were directly bound to the biochemical mode of action of an herbicide, other symptoms result from an indirect consequence of this action. The symptoms of herbicidal action deeply differed and that the climatic factors during the two first weeks after treatment could change definitely the result of the selective herbicide action. The repetitive observation of symptoms allows to inform the farmer about the tolerance or resistance of certain plant species, including the culture, for instance through the appearance of symptoms on the first leaves of the seedlings and their absence in the following leaves. As a whole, the accurate observation of herbicidal symptoms on plants is the essential, rapid and non-expensive analysis of treatment effectiveness at the field scale. The purpose of the current report is to describe the symptoms of a very complex herbicidal action, that of aclonifen involving two modes of action for the same molecule, approximately at the same concentration, and to compare these symptoms under field conditions and under controlled conditions, for a better understanding.